Understanding Strategy Implementation: Progress along Performance of Meru County Government in Kenya - Ntoiti, Kelvin Mutuma; Makau, Stephen Muathe (European Scientific Journal, ESJ, 2022)
Below-average performance is a characteristic that has been synonymous with many county governments in Kenya. The counties, formulate a County Integrated Development Plan as a guiding roadmap for five years. Besides the well-formulated strategies in Meru County, performance and effective service delivery have not been satisfactorily achieved. This study was designed to investigate strategy implementation and performance of the Meru County Government. The study’s specific objectives were; to determine the effects of resource allocation, organizational culture, leadership, and organizational structure on strategy implementation and performance of Meru County Government. The study targeted 291 employees of Meru County Government and a descriptive research design was used. Multiple regression analysis was used to analyze data. Findings indicated that resource allocation, organizational culture, leadership, and organizational structure had a positive and significant influence on the county government’s performance. The study recommends that; on resource allocation, the county government prioritize sufficient resource allocation on matters of strategy implementation, and create a wide and growing resource base to properly finance its activities. In organizational culture; mission and goals should be made clear at every level, and the culture should uphold goal attainment and promote easy communication during strategy implementation. In organizational leadership, the study recommends that the management should have more employees contribute to decision-making. Periodic workshops and/or training should be held for all employees. On the organizational structure; the county government can enhance its structure through participative decision-making, creating a simple and short chain of command for strategy implementation and promoting interdepartmental learning.